A digital environment for developing mathematical abilities in children with autism spectrum disorder - Santos, M. Isabel (2018)
This paperdescribes the several phases for the design and development of the digital Learning Environment on Mathematics for Autistic children (LEMA). LEMA is a prototype of a digital mathematical learning environment which activities are dynamically adapted to the user’s profile, towards the development of mathematical abilities of children aged 6–12 years diagnosed with autism spectrum disorders (ASD). This prototypehas already been evaluated with end-users (both students and teacher’s experts) and based on the analysis of the collected data readjustments were made, enabling the continuous improvement of the prototype, namely considering the integration of universal design for learning approaches, which are of most importance in ASD, due to its heterogeneity. The learning strategies incorporated in LEMA are also described.